The National Weather Service modernization and associated restructuring a retrospective assessment (National Academies Press, 2012)
"The Modernization and Associated Restructuring (MAR) of the National Weather Service (NWS) was a large and complex re-engineering of a federal agency. The process lasted a decade and cost an estimated 4.5 billion [dollars]. The result was greater integration of science into weather service activities and improved outreach and coordination with users of weather information. The MAR created a new, modernized NWS, and, significantly, it created a framework that will allow the NWS to keep up with technological changes in a more evolutionary manner. The MAR was both necessary and generally well executed. However, it required revolutionary, often difficult, changes. The procurement of large, complex technical systems presented challenges in and of itself. The MAR also affected the career paths and personal lives of a large portion of the field office workforce. The MAR created a new, modernized NWS, and, significantly, it created a framework that will allow the NWS to keep up with technological changes in a more evolutionary manner. The National Weather Service modernization and associated restructuring presents the first comprehensive assessment of the execution of the MAR and its impact on the provision of weather services in the United States. This report provides an assessment that addresses the past modernization as well as lessons learned to support future improvements to NWS capabilities"--Publisher's description.